2013
DOI: 10.1016/j.canlet.2012.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive DNA methylation and extensive mutation analyses reveal an association between the CpG island methylator phenotype and oncogenic mutations in gastric cancers

Abstract: Recent development of personal sequencers for extensive mutation analysis and bead array technology for comprehensive DNA methylation analysis have made it possible to obtain integrated pictures of genetic and epigenetic alterations on the same set of cancer samples. Here, we aimed to establish such pictures of gastric cancers (GCs). Comprehensive methylation analysis of 30 GCs revealed that the number of aberrantly methylated genes was highly variable among individual GCs. Extensive mutation analysis of 55 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 54 publications
0
48
0
Order By: Relevance
“…This mutation has been described in both meningioma (44) and gastric carcinoma (45). In ameloblastoma, this missense mutation did not alter (SMARCB1) INI-1 staining.…”
Section: Discussionmentioning
confidence: 61%
“…This mutation has been described in both meningioma (44) and gastric carcinoma (45). In ameloblastoma, this missense mutation did not alter (SMARCB1) INI-1 staining.…”
Section: Discussionmentioning
confidence: 61%
“…This study revealed that the Wnt pathway was potentially activated by aberrant methylation of its negative regulators, such as Dkk-3, NKD1, Sox17, WIF-1 and sFRP1. Moreover, DNA methylation and extensive mutation analyses in gastric cancers revealed an association between the CpG island methylator phenotype and oncogenic mutations in CTNNB1, ERBB2, KRAS and PIK3CA [150] . Downregulation of Sox10 by promoter methylation has also been detected in gastric cancer tissues [112] .…”
Section: Loss Of Wnt Repressor Function In Gastric Cancermentioning
confidence: 99%
“…A total of 56 primary GC samples (32 intestinal type and 24 diffuse type) were collected from surgical specimens of patients who had undergone gastrectomy, and 30 of the samples were used for our previous studies [1,16]. Genome-wide DNA methylation and TP53 mutation data of the 30 GCs were obtained from one of the studies [1].…”
Section: Gc Cell Lines and Tissue Samplesmentioning
confidence: 99%
“…Genome-wide DNA methylation and TP53 mutation data of the 30 GCs were obtained from one of the studies [1]. Peripheral leukocyte samples were collected from five healthy volunteers by a centrifugation method.…”
Section: Gc Cell Lines and Tissue Samplesmentioning
confidence: 99%
See 1 more Smart Citation